2020
DOI: 10.1007/s00265-020-02908-y
|View full text |Cite
|
Sign up to set email alerts
|

The fast and the curious II: performance, personality, and metabolism in Karoo bush rats

Abstract: Personality traits (e.g., activity, exploration, boldness) are frequently correlated with each other and with various other traits of biological importance. According to the performance, allocation, and independent models of energy management, the relationship between personality traits and resting metabolic rate (RMR) is predicted to be either positive, negative, or nil. As for the relationship between personality traits and locomotor performance, the trait compensation and co-specialisation hypotheses respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…In contrast with other bufonids, such as Rhinella marina , whose jumping distance is directly proportional to body length ( Hudson et al, 2020 ), sprint speed of E. calamita is unrelated to body size ( Zamora-Camacho, 2018 ), which allows for a separate evaluation of both parameters. The absence of correlations between speed and the behavioural traits tested as a part of this study is aligned with findings on Zootoca vivipara ( Le Galliard et al, 2013 ) and Phrinocephalus vlangalii lizards ( Chen et al, 2019 ), but not with findings on Myotomis unisulcatus ( Agnani et al, 2020 ) and Tamias striatus rodents ( Newar & Careau, 2018 ). It is worth mentioning that all toads in this sample engaged in flight behaviour.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast with other bufonids, such as Rhinella marina , whose jumping distance is directly proportional to body length ( Hudson et al, 2020 ), sprint speed of E. calamita is unrelated to body size ( Zamora-Camacho, 2018 ), which allows for a separate evaluation of both parameters. The absence of correlations between speed and the behavioural traits tested as a part of this study is aligned with findings on Zootoca vivipara ( Le Galliard et al, 2013 ) and Phrinocephalus vlangalii lizards ( Chen et al, 2019 ), but not with findings on Myotomis unisulcatus ( Agnani et al, 2020 ) and Tamias striatus rodents ( Newar & Careau, 2018 ). It is worth mentioning that all toads in this sample engaged in flight behaviour.…”
Section: Discussionsupporting
confidence: 80%
“…Novel tank diving variables had stronger positive correlations with the time in swim zone and time spent swimming than open field variables, suggesting that less-anxious fish were more motivated to be in the swim zone. High levels of exploration in the open field test have been associated with increased wheel running in different inbred strains of mice ( Careau et al, 2012 ) and slow sprinters in wild rats ( Agnani et al, 2020 ). In the current study, the relationship between novel tank diving variables and swimming behavior were relatively weak, thus more evidence is needed to further corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Still, other studies support the independent hypothesis of energy management in that they found no significant relationship between personality and RMR ( e.g. , Bouwhuis et al, 2014 ; Videlier, Rundle & Careau, 2019 ; Agnani et al, 2020 ). Consequently, the relationships between intraspecific RMR, body mass/body size and animal personality traits remain largely unclear.…”
Section: Introductionmentioning
confidence: 91%